Tension on the thin blue line: Police officer resistance to community-oriented policing - Dicker, Todd J. (American journal of criminal justice, 1998)
While over 60% of police agencies in the United States are either implementing or planning for community policing (Annan, 1995), actual implementation of community policing practices is disjointed and has produced more problems than solutions. One such problem is the resistance among officers to the philosophy itself. In a study of the orientations of noncommunity policing officers in the largest public safety department in the US, it is determined that elements of the organizational culture of the police agency are not significant predictors of support for the community policing philosophy. Rather, individual orientations toward citizen involvement in crime prevention and job involvement are predictors of officer support. Implications for police managers are discussed.